Pulmonary endarterectomy for patients with chronic thromboembolic disease - (:unkn) unknown (TURKISH SOC CARDIOLOGY, 2018)
Objective: Chronic thromboembolic disease (CTED) is characterized by persistent pulmonary thromboembolic occlusions without pulmonary hypertension. Early surgical treatment by performing pulmonary endarterectomy (PEA) may improve symptoms. The goal of the study was to review our experience and early outcome of PEA in patients with CTED. Methods: Data were prospectively collected on all patients who underwent PEA between 2011 and 2015. Patients with CTED and a mean pulmonary artery pressure (mPAP) of <25 mm Hg were identified. All patients were in New York Heart Association (NYHA) functional class II or III. Measured outcomes were in-hospital complications, improvement in cardiac function and exercise capacity, and survival after PEA. Patients were reassessed at 6 months following surgery. Results: A total of 23 patients underwent surgery. There was no in-hospital mortality, but complications occurred in six patients (26%). At 6 months following surgery, 93% of the patients remained alive. Following PEA, the mPAP fell significantly from 21.0 +/- 2.7 mm Hg to 18.2 +/- 5.5 mm Hg (p<.001). Pulmonary vascular resistance also significantly decreased from 2.2 +/- 0.7 wood to 1.5 +/- 0.5 wood (p<.001). The 6-min walking distance significantly increased from 322.6 +/- 80.4 m to 379.9 +/- 68.2 m (p<.001). There was a significant symptomatic improvement in all survivors in NYHA functional classes I or II at 6 months following surgery (p=.001). Conclusion: PEA in selected patients with CTED resulted in significant improvement in symptoms. The selection of patients for undergoing PEA in the absence of pulmonary hypertension must be made based on patients' expectations and their acceptance of the perioperative risk.
Keywords: chronic thromboembolic disease; pulmonary endarterectomy; mortality; outcome; HYPERTENSION; EMBOLISM; OBSTRUCTION; MANAGEMENT; EXERCISE